A comparative study of design sensitivity analysis based on adjoint variable method for transient response of non-viscously damped systems. (15th September 2018) - Ding, Zhe; Li, Li; Li, Xiaobai; Kong, Jianyi
Highlights: Adjoint variable sensitivity analysis for non-viscously damped system is presented. The design sensitivity analysis is for transient response. Discretize-then-differentiate and differentiate-then-discretize approaches are introduced. The computational considerations of the methods are investigated and compared. Two examples are given to show the performances of the two methods. Abstract: In this paper, design sensitivity analysis methods for the transient response of non-viscously damped systems are considered. The damping forces of the non-viscously damped systems depend on the past history of motion via convolution integrals over some suitable kernel functions. The adjoint variable method (AVM) is adopted to develop the design sensitivity analysis. Two numerical solution schemes, namely the discretize-then-differentiate method and the differentiate-then-discretize method, are introduced to complete the AVM for the sensitivity analysis of non-viscously damped systems. The discretize-then-differentiate AVM discretizes the equations of motion based on the Newmark- β implicit integration method first and then differentiates the discrete equations. On the contrary, the differentiate-then-discretize AVM firstly differentiates the equations of motion after transforming it into a state-space form, and then discretizes the equations based on a modified precise integration method (PIM). The numerical accuracy, efficiency, consistency and implementation effort are discussed and compared. Two numerical examples are presented to show the effectiveness of both methods. The results indicate that, by considering both computational accuracy and efficiency, the PIM based differentiate-then-discretize method is more suitable than the Newmark- β based discretize-then-differentiate method for the sensitivity analysis of transient responses for non-viscously damped systems.